Prognostic factors for trigeminocardiac reflex during cerebrovascular intervention operation - Sun, Zhaochu; Bhuiyan, Piplu; Lu, Hua; Qian, Yanning; Xiao, Hang (Frontiers in Surgery, 2022)
Introduction Trigeminocardiac reflex (TCR) is a brainstem reflexive response of hemodynamic instability during surgery. Identification of risk factors relevant to TCR during cerebrovascular intervention procedures is helpful to efficiently prevent and treat its occurrence. The purpose of this study was to demonstrate the risk factors for Onyx embolization during cerebrovascular intervention operation so as to optimize perioperative management strategies on TCR. Methods We performed a retrospective study on the patients with Onyx embolization under general anaesthesia over 6-years period from 2013 to 2018. 354 patients were finally eligible for inclusion, and then divided into TCR group (group T) and control group (group N). Patient characteristics, clinical diagnosis, comorbidities, lesion sites, hemodynamics changes, and complications were compared between two groups. Several multivariable regression models were applied to analyze the risk factors associated with TCR. Results TCR occurred in 59 patients (16.7%) among 354 patients. There was no significant difference in patient characteristics between two groups (P > 0.05). During DMSO/Onyx injection, HR and MAP were much lower in group T than group N (P < 0.01). Notably, univariable analysis revealed that the patients with dural arteriovenous fistula (DAVF) and middle meningeal artery being affected were associated with a higher incidence of TCR (P < 0.01). Furthermore, multivariable analysis showed that there was a close link of TCR with DAVF [OR = 4.12; 95% CI (1.83–10.65)] and middle meningeal artery embolization [OR = 3.90; 95% CI (1.58–9.63)]. Further stratified analysis of patients with TCR found that patients with middle meningeal artery embolization were more likely to experience hypotension during TCR episode (P < 0.05). Finally, more incidence of postoperative adverse events was observed when TCR episode (P < 0.05). Conclusion We found that DAVF and middle meningeal artery embolization were independent risk factors for TCR episodes during Onyx endovascular embolization, highly likely leading to intraoperative hemodynamics fluctuations and postoperative adverse events.